2019
DOI: 10.1530/erc-19-0083
|View full text |Cite
|
Sign up to set email alerts
|

How and when to use temozolomide to treat aggressive pituitary tumours

Abstract: Temozolomide is an oral chemotherapy used to treat aggressive pituitary tumours since 2006. It is inexpensive and well tolerated, the main side effects are fatigue, nausea and cytopenia. Overall the studies demonstrate approximately 70% response rate for temozolomide, if response is defined radiologically as complete, partial response or stable disease. Using the more stringent criteria of complete or partial response, the success rate is near 40%. Functioning tumours respond more frequently than non-functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
2
14
0
2
Order By: Relevance
“…Recently, an international survey of clinical practice (27) recommended temozolomide as first line chemotherapeutic treatment of aggressive pituitary tumors or pituitary carcinomas. As previous reported, 69% (28) of patients could obtain complete response, partial response or stable disease. The success rate of clear tumor volume reduction (complete response or partial response) was 42% (28).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, an international survey of clinical practice (27) recommended temozolomide as first line chemotherapeutic treatment of aggressive pituitary tumors or pituitary carcinomas. As previous reported, 69% (28) of patients could obtain complete response, partial response or stable disease. The success rate of clear tumor volume reduction (complete response or partial response) was 42% (28).…”
Section: Discussionsupporting
confidence: 71%
“…As previous reported, 69% (28) of patients could obtain complete response, partial response or stable disease. The success rate of clear tumor volume reduction (complete response or partial response) was 42% (28). There was rare data about radiotherapy for aggressive pituitary adenomas.…”
Section: Discussionsupporting
confidence: 71%
“…However, some recent studies have suggested that early use of temozolomide in these patients could result in a better outcome ( 88 , 121 ). In this regard, high-grade tumors on MRI, such as invasiveness and increasing tumor size, and pathological findings, including high MIB1-labeling index, could be a sign of temozolomide initiation after surgery under RT ( 130 , 131 ). However, patients administered with temozolomide in the early stage are relatively rare.…”
Section: Treatmentmentioning
confidence: 99%
“…Tumors resistant to TMZ chemotherapy have been shown in a certain number of refractory pituitary tumors ( 130 ). Thus, a predictive marker for resistance to temozolomide needs to be identified.…”
Section: Treatmentmentioning
confidence: 99%
“…Obviously, the effect of TMZ treatment has a strong correlation with the expression of MGMT in glioma (24,25). Specifically, the lower the degree of MGMT expression, the better the tumor's response to TMZ treatment.…”
Section: Discussionmentioning
confidence: 99%